Glosarium antropologi - Jacob, T., 1929-; Ruskhan, Abdul Gaffar; Sutiman (Jakarta : Pusat Bahasa, Departemen Pendidikan Nasional, 2004)
English-Indonesian dictionary of anthropological terms
English and Indonesian
Keywords: Anthropology -- Terminology -- Indonesian; Anthropology -- Dictionaries -- Indonesian; Indonesian language -- Glossaries, vocabularies, etc